2013
DOI: 10.1515/hsz-2013-0106
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid suppresses NGAL-induced epithelial-to-mesenchymal transition in melanoma

Abstract: Betulinic acid (BA) exhibits antitumoral activity by blocking proliferation, invasion, and angiogenesis. However, the impact of BA on epithelial-to-mesenchymal transition (EMT), a hallmark of cancer metastasis induced among others by neutrophil gelatinase-associated lipocalin (NGAL), remains unknown. The present study aimed at determining the effect of BA on NGAL-induced EMT. In A375 melanoma cells, BA downregulated mesenchymal markers, increased epithelial markers, and inhibited cytoskeletal reorganization. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…In contrast, the knockdown of Lcn2 in MDA-MB-231 breast cancer cells reverses EMT, associated with reduced tumour growth and metastasis [9]. In line with this, we recently described that Lcn2 conveys EMT characteristics to A375 melanoma cells, enhancing migration and invasion [15]. Moreover, the use of mouse mammary tumour Stroma-derived Lcn2 and metastasis 275 cells, whereas the possibility that Lcn2 is provided by tumour-infiltrating immune cells, such as neutrophils or macrophages, has not so far been taken into account.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, the knockdown of Lcn2 in MDA-MB-231 breast cancer cells reverses EMT, associated with reduced tumour growth and metastasis [9]. In line with this, we recently described that Lcn2 conveys EMT characteristics to A375 melanoma cells, enhancing migration and invasion [15]. Moreover, the use of mouse mammary tumour Stroma-derived Lcn2 and metastasis 275 cells, whereas the possibility that Lcn2 is provided by tumour-infiltrating immune cells, such as neutrophils or macrophages, has not so far been taken into account.…”
Section: Introductionmentioning
confidence: 77%
“…In contrast, the knockdown of Lcn2 in MDA‐MB‐231 breast cancer cells reverses EMT, associated with reduced tumour growth and metastasis . In line with this, we recently described that Lcn2 conveys EMT characteristics to A375 melanoma cells, enhancing migration and invasion . Moreover, the use of mouse mammary tumour models showed that Lcn2 −/− mice developed significantly fewer tumours, but differences in metastasis are still controversially discussed .…”
Section: Introductionmentioning
confidence: 77%
“…On account of our group expertise in the field of skin pathologies (Dehelean et al, 2013, 2016; Gheorgheosu et al, 2013; Soica et al, 2014; Danciu et al, 2015), the present study could be seen as a first step in the synthesis and characterization of the magnetic iron nanoparticles double coated with oleic acid as future carrier platforms for transdermal drug delivery in skin malignancies (melanoma and non-melanoma skin cancers, auto-immune diseases—epidermolysis bullosa acquisita). In this regard was evaluated the toxicological profile of the colloidal suspensions on human keratinocytes cell line and by applying the dermal acute test to SKH-1 hairless mice.…”
Section: Discussionmentioning
confidence: 99%
“…The antitumor effects of BA are related to the downregulation of cycli D and Bcl-xL expressions [13]. Studies have demonstrated that BA shows antimetastatic effects by inhibiting epithelial mesenchymal transition (EMT) [14]. Several studies have also suggested that BA has anti-angiogenic activity by disturbing the binding of HIF-1α and STAT3 to the VEGF promoter in hypoxic PC-3 cells [15].…”
Section: Introductionmentioning
confidence: 99%